Penguatan Karakter Remaja melalui Nilai-Nilai Keagamaan sebagai Upaya Pencegahan Kenakalan Remaja - Meidinata, Erlando; Miftahurrohmah, Septina; Mawadati, Zakyna; Rochim, Ahmad Faisal; Anfanani, Anfan; Fadilah, Fiki Nur Fatihatul; Susilowati, Lusiana Sri; Hati, Intan Tyara; Chusna, Irma Roudlotul; Rifaza, Rizkika; Kusuma, Nurma Ayu; Fatimah, Siti; Roudhoh, Siti; Agustin, Afifah Dwi; Khotimah, Putri Kusnul; Utami, Nur Fadilah; Alfarizki, M. Wahyu; Febrianto, Muhammad Aldy; Robingatun, Robingatun (Welfare : Jurnal Pengabdian Masyarakat, 2024)
Juvenile delinquency is an issue that requires serious attention because it can impact the social and moral life of adolescents. This activity aims to strengthen adolescent character through the application of religious values as an effort to prevent juvenile delinquency in Keniten Village, Mojo District, Kediri Regency. The community service method uses a participatory approach, which involves lecture sessions, group discussions, and simulations to understand and internalize religious values. This activity was attended by 30 adolescents, with the support of local religious figures as facilitators, and lasted for one day at the Keniten Village Hall. The results of the community service showed an increase in participants' understanding of the importance of religious values in forming positive character and responsible behavior. In addition, participants were able to recognize the negative impacts of juvenile delinquency and demonstrated a commitment to practicing religious values in everyday life. This program is expected to be the first step in building a young generation with character and harmony in society.